Aural comprehension in young learners’ foreign language development - Mihaljević Djigunović, J.; Lopriore, L. (2012)
While research on listening as a FL skill has traditionally been product-oriented, recent studies have investigated aural comprehension processes in FL learning in terms of constructing and communicating meaning. In early FL learning listening provides the basic input for literacy development: it is through oral language that the foundation for learning a new language is established. This contribution describes a longitudinal study on the development of aural comprehension skills in English as a FL of Croatian and Italian young learners. The authors hypothesised that early aural development would be characterised by individual learner differences and by contextual differences. The sample included 361 learners who were followed for four years. Each year participants’ aural comprehension was measured by listening tasks of increasing linguistic and cognitive complexity. The tasks required learners to identify specific words, comprehend language chunks and relate them to a communicative context illustrated in sets of pictures. Listening tasks results were considered against learner perception of task difficulty and what helped or hindered their comprehension, and against their attitudes to teaching, motivation for learning, linguistic self-concept as well out-of-school exposure to English. Findings support the starting hypothesis: early aural development is associated with individual and contextual differences.
Projekt MZOS
ENG